2010
DOI: 10.1016/j.jocn.2009.07.103
|View full text |Cite
|
Sign up to set email alerts
|

MMP-9 levels in elderly patients with cognitive dysfunction after carotid surgery

Abstract: Approximately 25% of elderly patients scheduled for carotid endarterectomy (CEA) develop post-operative cognitive dysfunction (CD). We tested the hypothesis that the plasma levels of matrix metalloproteinase 9 (MMP-9) are predictive of moderate to severe CD after CEA. A total of 73 patients were prospectively enrolled in this Institutional Review Board approved study. Plasma samples were obtained at baseline and day 1 post-surgery. We measured the plasma concentrations of both MMP-9 and its inhibitor, tissue i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 24 publications
0
14
0
Order By: Relevance
“…Serum MMP-9 levels have been shown to be positively correlated with the severity of cognitive impairment [19]. Gaudet reported that POCD in elderly patients after cardiac surgery was related to increased MMP-9 levels [20]. The present study showed that the serum MMP-9 levels at T1, T2, T3, and T4 in the POCD group were significantly higher than the levels at T0, while the levels in the non-POCD group returned to preoperative levels at T3.…”
Section: Discussionmentioning
confidence: 99%
“…Serum MMP-9 levels have been shown to be positively correlated with the severity of cognitive impairment [19]. Gaudet reported that POCD in elderly patients after cardiac surgery was related to increased MMP-9 levels [20]. The present study showed that the serum MMP-9 levels at T1, T2, T3, and T4 in the POCD group were significantly higher than the levels at T0, while the levels in the non-POCD group returned to preoperative levels at T3.…”
Section: Discussionmentioning
confidence: 99%
“…121 A prospective cohort study identified that patients with cognitive dysfunction after carotid surgery had higher pre-and postoperative plasma levels of MMP-9 than those without cognitive symptoms. 122 Postoperative increments of MMP-9 can represent systemic inflammatory response, local release of the protein due to atherosclerotic plaque manipulation, microembolization, or transient ischaemia with resulting BBB damage. 123 However, the finding of higher preoperative concentrations in patients who developed POCD may represent also a higher 'baseline' inflammatory state or silent areas of ischaemia associated with subclinical BBB dysfunction.…”
Section: Metalloproteinasesmentioning
confidence: 99%
“…Markers examined by our group that have been shown to correlate with CD include S100β, 3 monocyte chemoattractant protein 1 (MCP-1), 20 induced nitric oxide synthase (iNOS), 36 APOE-E4, 17 and matrix metalloproteinase 9 (MMP9). 10 We have also identified specific SNPs that have correlated with CD. The presence of at least one APOE -E4 allele has been associated with increased risk of CD at 1 month after CEA.…”
Section: Discussionmentioning
confidence: 97%